Development of cutter for printed circuit board using hydraulic principle - Mohd Muhaymin, Ismail (2007)
Cutter was known since long times ago as something that was use to cut the thing into smaller piece. Starting from the usual rock at the rock age till the high technology cutter which was make from the precious and valuable material like diamond at this modern age, the cutter was develop to make our daily life more easier and easier. This project is proposed to design and fabricate a cutter as benefit to cut the printed circuit board, the board which contains cuprum as a trace to connect the electricity current to the electronic component like resistors and capacitors. The printed circuit board was widely used in modern electronic and electric component like radio and computer because it can minimize the space and reduce the manufacturing cost by assemble all electronic components together. The usual way to cut the printed circuit board is by using hand because the sensitive of it. By develop the cutter it will make the way to cut the printed circuit board is more efficient without give the damage to the board. In this project, the main purpose of study is to develop the cutter to make sure the cutter can achieve it objective. Developments of cutter are starting by choosing the right cutter's material then design and finally fabricate the cutter.